Comparison of the Prognostic Value of PET Metabolic Parameters and Postoperative Pathologic Response After Neoadjuvant Immunochemotherapy in Non–Small Cell Lung Cancer - You Cheng; Tian Qin; Fan Yang; Kaiyu Lu; Haoyu Zhu; Dan Shao (Clinical Nuclear Medicine, 2026)
Objective: This study aimed to evaluate the prognostic value of serial PET/CT metabolic parameters and postoperative pathologic response separately, compare their predictive performance, and further assess their combined prognostic value in patients with non–small cell lung cancer (NSCLC) undergoing neoadjuvant immunotherapy plus chemotherapy. Methods: We retrospectively analyzed 219 NSCLC patients who received neoadjuvant immunotherapy plus chemotherapy, followed by surgery. Pre- and post-treatment PET/CT metabolic parameters assessed by iPERCIST and postoperative pathologic response were collected. Their associations with disease-free survival (DFS) were evaluated using ROC and Kaplan-Meier analyses. Results: During a median follow-up of 24.9 months, 59 patients (26.9%) experienced recurrence. PET metabolic parameters, particularly post-treatment parameters and their percentage changes (ΔPET), demonstrated significant prognostic value for DFS. According to iPERCIST, patients achieving imaging complete metabolic response (iCMR) demonstrated superior DFS compared with non-iCMR patients (median DFS not reached vs. 44.9 mo, P =0.001). Similarly, patients achieving pathologic complete response (pCR) or major pathologic response (MPR) showed improved DFS ( P =0.008 and 0.002, respectively). Combined stratification demonstrated that patients with both iCMR and pCR had the most favorable outcomes compared with other groups ( P =0.003). Conclusions: Serial PET metabolic parameters and postoperative pathologic response hold significant prognostic value following neoadjuvant immunotherapy plus chemotherapy in NSCLC. The combination of serial PET metabolic parameters and postoperative pathologic response in a joint model improves prognostic prediction in NSCLC following neoadjuvant immunotherapy plus chemotherapy.